PENGEMBANGAN DATA MART UNTUK ANALISIS PENDAPATAN PELAYANAN RUMAH SAKIT - , Yusak Wibowo Mihardjo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Developing data mart is an activity aimed at digging for further historical data of the existing operation. The result of data digging is to find out the condition that has occurred and to make it a recommendation for the betterment of strategic planning for an organization, no matter what, including hospital in the long run. The design of hospital data mart is made, but it is limited to focusing on the research of revenue trend by using historical data existing on the hospital information system. The result of this research is expected to be able to contribute information for the management. The information deals with the activities and effectiveness of the service task force in financial contribution to the hospital. The research result is in the form of data mart development containing the analysis of revenue trend from both the services of in-patients and out-patients, such as revenue trend based on class, contribution of supporting task force, origin of most patients, and doctorsâ specialization. The revenue trend is also based on the kinds of most diseases or what surgical interventions contributing most to revenue.